Perceived Social Support Protects Lonely People Against COVID-19 Anxiety: A Three-Wave Longitudinal Study in China - Xu, Jianjie; Ou, Jingyi; Luo, Shuyi; Wang, Zhuojun; Chang, Edward; Novak, Claire; Shen, Jingyi; Zheng, Shaoying; Wang, Yinan (Frontiers in Psychology, 2020)
The isolation to prevent the spread of the coronavirus disease 2019 (COVID-19) pandemic can give rise to anxiety, especially for lonely people who often feel upset without others’ company. Although being isolated from others, people can still perceive other’s support, which might lower their COVID-19 anxiety. To examine the relationship among loneliness, perceived social support, and anxiety, we measured 222 Chinese participants’ (54.50% female, Mage = 31.53, SD = 8.17) trait loneliness, chronic anxiety before the outbreak, state COVID-19 anxiety at the peak and decline stages of the COVID-19, and their perceived social support across the three time points. The results showed that people’s perceived social support dramatically increased from the pre-pandemic to the peak COVID-19 stage, and kept stable at the decline COVID-19 stage. In contrast, COVID-19 anxiety decreased from the peak to the decline stage. Further, perceived social support consistently moderated the relationship between loneliness with both chronic anxiety and state COVID-19 anxiety. The current study provides initial evidence that perceived social support provides protection for lonely people in daily life as well as unexpected disaster, which will contribute to finding ways to alleviate lonely people’s anxiety during the global health crisis.